Strategi Guru Dalam Meningkatkan Nilai Religius Siswa - Kerina, Malem; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Religious values are belief values that originate from a person's belief in God within oneself. Religious values are very necessary and useful to implement because they are in the form of a person's attitudes and behavior, especially for students who are obedient to religious teachings in everyday life. In this research, teachers must have an important role in instilling and fostering students' religious values so that students have good attitudes and characteristics. In this research, students are expected to have good religious values and have noble character in everyday life, especially in the school, family and community environment. Teacher strategies in increasing students' religious values are very important for every teacher, especially Hindu Religious Education teachers, so that it is easy to create religious or religious values for each student. The results obtained from this research are that students can form religious values obtained from various strategies of a teacher, especially Hindu religious education teachers, who slowly form religious values in students indirectly. Students can live/coxist with friends who have different beliefs, but these differences will not exist for students who succeed in instilling religious (religious/divine) values within themselves.